Prevalence of teenage pregnancy and its associated factors in high fertility sub-Saharan Africa countries: a multilevel analysis - Desale Bihonegn Asmamaw; Tesfahun Zemene Tafere; Wubshet Debebe Negash (BMC, 2023)
Abstract Background Teenage pregnancies are persistently high among adolescent women in high fertility countries in sub-Saharan Africa. It has been attributed to the high unmet need for family planning in this population. The aim of this study was to determine the prevalence and factors associated with teenage pregnancy in high fertility countries in sub-Saharan Africa. Methods Data for this study was obtained from the most recent Demographic and Health Surveys. A total weighted sample of 33,391 adolescent girls who had ever had sexual contact were included. A multilevel mixed-effect binary logistic regression model was fitted to identify the significant associated factors for teenage pregnancy. Finally, the Adjusted Odds Ratio (AOR) with a 95% confidence interval was used to declare as statistically significant. Results The overall teenage pregnancy in sub-Saharan Africa high frtility countries was 24.88% (95% CI, 24.42, 25.35). Educational status; no formal education (AOR = 1.39, 95% CI, 1.23, 1.56) and primary education (AOR = 1.45, 95% CI, 1.30, 1.62), not working (AOR = 1.32, 95% CI, 1.21, 1.45), being married (AOR = 67.88, 95% CI, 61.33, 75.12), poor (AOR = 1.47, 95% CI, 1.32, 1.65) and middle wealth quantile (AOR = 1.21, 95% CI, 1.07, 1.35), knowledge about contracptives (AOR = 2.45, 95% CI, 2.19, 2.74), unmet need for family planning (AOR = 2.42, 95% CI, 2.14, 2.74), Angola (AOR = 9.59, 95% CI, 7.82, 11.77), Chad (AOR = 3.05, 95% CI, 2.49, 3.74), DR.Congo (AOR = 3.77, 95% CI, 3.06, 4.65), and Mali (AOR = 1.84, 95% CI, 1.47, 2.28) were factors significantly associated with teenage pregnancy. Conclusions This study found that teenage pregnancy remains a common public health problem in the study areas. Level of education, marital status, occupation, wealth index, unmet need for family planning, knowledge about contraceptives, and country were significantly associated with teenage pregnancy. Hence, for sustainable development goal 3 to be realized by 2030, there must be investment in policy implementation and evaluation, as well as engagement with stakeholders in adolescents' sexual and reproductive health.